Applicability of Longitudinal Strain of Left Ventricle in Unstable Angina - Santos,Natasha Soares Simões dos (2018)
Abstract Background: Unstable angina (UA) is a common cause of hospital admission; risk stratification helps determine strategies for treatment. Objective: To determine the applicability of two-dimensional longitudinal strain (SL2D) for the identification of myocardial ischemia in patients with UA. Methods: Cross-sectional, descriptive, observational study lasting 60 days. The sample consisted of 78 patients, of which fifteen (19.2%) were eligible for longitudinal strain analysis. The value of p < 0.05 was considered significant. Results: The group of ineligible patients presented: a lower proportion of women, a higher prevalence of diabetes mellitus (DM), use of ASA, statins and beta-blockers and larger cavity diameters. The main causes of non-applicability were: presence of previous infarction (56.4%), previous CTA (22.1%), previous MRI (11.5%) or both (16.7%) and the presence of specific electrocardiographic abnormalities (12.8%). SL2D assessment revealed a lower global strain value in those with stenosis greater than 70% in some epicardial coronary arteries (17.1 [3.1] versus 20.2 [6.7], with p = 0.014). Segmental strain assessment showed an association between severe CX and RD lesions with longitudinal strain reduction of lateral and inferior walls basal segments; (14 [5] versus 21 [10], with p = 0.04) and (12.5 [6] versus 19 [8], respectively). Conclusion: There was very low SL2D applicability to assess ischemia in the studied population. However, the global strain showed a correlation with the presence of significant coronary lesion, which could be included in the UA diagnostic arsenal in the future.